2018
DOI: 10.2478/sjph-2018-0019
|View full text |Cite
|
Sign up to set email alerts
|

What can we learn from each other about undergraduate medical education in general practice/family medicine?

Abstract: IntroductionThere is a dearth of published literature on the organisation of family medicine/general practice undergraduate teaching in the former Yugoslavia.MethodsA semi-structured questionnaire was sent to the addresses of 19 medical schools in the region. Questions covered the structure of Departments of Family Medicine (DFM), organisation of teaching, assessment of students and their involvement in departmental activities.ResultsThirteen medical schools responded, of which twelve have a formal DFM. Few DF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The change brought significant challenges to both teachers and students, with a need to master new skills and adapt to new student-group dynamics while ensuring that learning objectives were met and quality and safety of medical education preserved [ 5 , 6 ]. Similar to other countries, the seven countries of the former Yugoslavia (Bosnia and Herzegovina, Croatia, Kosovo, Montenegro, North Macedonia, Serbia and Slovenia) had to undergo the transition to distance education in family medicine during the COVID-19 pandemic, given that family medicine is a standard part of undergraduate medical education and is also offered as a postgraduate training programme [ 7 , 8 ]. In our cross-sectional descriptive study of the transition from face-to-face to distance education in family medicine during COVID-19, among the countries of the former Yugoslavia, we found that despite limited preparedness, teachers and students made the transition to predominantly synchronous online teaching but struggled with online assessment and practical skills’ classes.…”
Section: Introductionmentioning
confidence: 99%
“…The change brought significant challenges to both teachers and students, with a need to master new skills and adapt to new student-group dynamics while ensuring that learning objectives were met and quality and safety of medical education preserved [ 5 , 6 ]. Similar to other countries, the seven countries of the former Yugoslavia (Bosnia and Herzegovina, Croatia, Kosovo, Montenegro, North Macedonia, Serbia and Slovenia) had to undergo the transition to distance education in family medicine during the COVID-19 pandemic, given that family medicine is a standard part of undergraduate medical education and is also offered as a postgraduate training programme [ 7 , 8 ]. In our cross-sectional descriptive study of the transition from face-to-face to distance education in family medicine during COVID-19, among the countries of the former Yugoslavia, we found that despite limited preparedness, teachers and students made the transition to predominantly synchronous online teaching but struggled with online assessment and practical skills’ classes.…”
Section: Introductionmentioning
confidence: 99%